Current trends in patients with chronic total occlusions undergoing coronary CT angiography. Issue 15 (15th June 2015) - Opolski, Maksymilian P; ó Hartaigh, Bríain; Berman, Daniel S; Budoff, Matthew J; Achenbach, Stephan; Al-Mallah, Mouaz; Andreini, Daniele; Cademartiri, Filippo; Chang, Hyuk-Jae; Chinnaiyan, Kavitha; Chow, Benjamin J W; Hadamitzky, Martin; et al.
Abstract : Objective: Data describing the prevalence, characteristics and management of coronary chronic total occlusions (CTOs) in patients undergoing coronary CT angiography (CCTA) have not been reported. The purpose of this study was to determine the prevalence, characteristics and treatment strategies of CTO identified by CCTA. Methods: We identified 23 745 patients who underwent CCTA for suspected coronary artery disease (CAD) from the prospective international CCTA registry. Baseline clinical data were collected, and allocation to early coronary revascularisation performed within 90 days of CCTA was determined. Multivariable hierarchical mixed-effects logistic regression reporting OR with 95% CI was performed. Results: The prevalence of CTO was 1.4% (342/23 745) in all patients and 6.2% in patients with obstructive CAD (≥50% stenosis). The presence of CTO was independently associated with male sex (OR 3.12, 95% CI 2.39 to 4.08, p<0.001), smoking (OR 2.02, 95% CI 1.55 to 2.64, p<0.001), diabetes (OR 1.60, 95% CI 1.22 to 2.11, p=0.001), typical angina (OR 1.51, 95% CI 1.12 to 2.06, p=0.008), hypertension (OR 1.47, 95% CI 1.14 to 1.88, p=0.003), family history of CAD (OR 1.30, 95% CI 1.01 to 1.67, p=0.04) and age (OR 1.06, 95% CI 1.05 to 1.07, p<0.001). Most patients with CTO (61%) were treated medically, while 39% underwent coronary revascularisation. In patients with severe CAD (≥70% stenosis), CTO independently predicted revascularisation by coronary artery bypass grafting (OR 3.41, 95% CI 2.06 to 5.66, p<0.001), but not by percutaneous coronary intervention (p=0.83). Conclusions: CTOs are not uncommon in a contemporary CCTA population, and are associated with age, gender, angina status and CAD risk factors. Most individuals with CTO undergoing CCTA are managed medically with higher rates of surgical revascularisation in patients with versus without CTO. Trial registration number: ClinicalTrials.gov identifier NCT01443637 .